Pre-lithiated negative electrode sheet and preparation method and application thereof

CN123017881APending Publication Date: 2026-10-30TSINGHUA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611092473.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]相关技术中,预锂化工艺已发展出多种技术路径,但普遍存在锂源利用率低、对环境水分高度敏感、预锂化程度难以精确调控、与传统极片制造工艺兼容性差等问题

Benefits of technology

[0004]本申请旨在至少在一定程度上解决相关技术中的技术问题之一。为此,本申请提供了一种预锂化负极片及其制备方法与应用。该方法能够精确调控预锂化程度,具有锂源利用效率高、环境兼容性好、工艺简单等特点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion battery materials, and specifically discloses a pre-lithiated negative electrode sheet and a preparation method and application thereof. The pre-lithiated negative electrode sheet comprises a negative electrode matrix and a coating arranged on at least part of the surface of the negative electrode matrix; the coating comprises a porous carbon framework, the porous carbon framework has a connected pore, the connected pore is connected with the outside of the coating, and a pre-lithiation reagent is embedded in the wall of the porous carbon framework. The method can accurately control the pre-lithiation degree, and has the characteristics of high lithium source utilization efficiency, good environmental compatibility, simple process and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery materials technology, specifically to pre-lithiated anode sheets, their preparation methods, and applications. Background Technology

[0002] In lithium-ion batteries, during the first charge, the electrolyte undergoes a reduction decomposition reaction on the negative electrode surface, forming a solid electrolyte interphase (SEI) film. This film formation process irreversibly consumes a large number of active lithium ions, resulting in an initial coulombic efficiency (ICE) typically only 85%–92%, reducing the battery's energy density and cycle life. To compensate for this irreversible lithium loss, pre-lithiation technology has been extensively studied.

[0003] In related technologies, pre-lithiation processes have developed into various technical paths, but they generally suffer from problems such as low lithium source utilization, high sensitivity to environmental moisture, difficulty in precisely controlling the degree of pre-lithiation, and poor compatibility with traditional electrode manufacturing processes. Therefore, it is necessary to develop a pre-lithiation method with high lithium source utilization, good environmental compatibility, uniform and controllable pre-lithiation, and compatibility with existing production lines. Summary of the Invention

[0004] This application aims to at least partially address one of the technical problems in related technologies. To this end, this application provides a pre-lithiated anode sheet, its preparation method, and its application. This method can precisely control the degree of pre-lithiation and features high lithium source utilization efficiency, good environmental compatibility, and simple process.

[0005] The first aspect of this application provides a pre-lithiated negative electrode, comprising: Negative electrode substrate; and A coating disposed on at least a portion of the surface of the negative electrode substrate; The coating comprises a porous carbon skeleton having interconnected pores that communicate with the outside of the coating, and a pre-lithiation reagent is embedded in the wall of the porous carbon skeleton.

[0006] Therefore, by connecting the pores, the pre-lithiated negative electrode plate serves two purposes: firstly, it acts as a rapid permeation channel for the electrolyte during the electrolyte injection stage, significantly shortening the static activation time; secondly, it serves as a transport channel for lithium-ion insertion / extraction and a release space for volume expansion during electrochemical cycling. The pre-lithiation reagent is encapsulated within the porous carbon framework, preventing deactivation during processing and storage; the lithium replenishment process is carried out uniformly, avoiding local over-lithiation or under-lithiation problems; the carbon framework, as a physical isolation layer, facilitates the relaxation of dew point requirements in the production environment, significantly improving operational safety. More importantly, the interconnected pores and the embedded pre-lithiation reagent are independent yet synergistic, giving the coating both excellent air storage stability and rapid electrochemical activation response. This results in high lithium source utilization and controllable pre-lithiation levels, overcoming the traditional bias that better protection in pre-lithiation coatings leads to slower activation, thus improving initial coulombic efficiency and significantly extending cycle life.

[0007] According to the embodiments of this application, the aforementioned pre-lithiated negative electrode sheet may further include at least one of the following additional technical features: In some embodiments, the pre-lithiated negative electrode sheet satisfies at least one of the following conditions: The negative electrode substrate includes at least one of carbon-based negative electrode substrate, silicon-based negative electrode substrate, tin-based negative electrode substrate, or a composite negative electrode substrate thereof; preferably, the negative electrode substrate is a graphite negative electrode substrate; The pre-lithiation reagent includes at least one of stabilized lithium metal (SLMP), lithium hydride (LiH), lithium silicon alloy, lithium tin alloy, and lithium aluminum alloy. The average particle size of the pre-lithiation reagent is 10 nm to 50 μm, preferably 1 to 100 μm.

[0008] In some embodiments, the pre-lithiated negative electrode sheet satisfies at least one of the following conditions: The porous carbon framework has a BET specific surface area of ​​50~400 m². 2 / g, preferably 100~300 m 2 / g; The porous carbon framework has a pore size of 2~50 nm, preferably 5~30 nm; The porosity of the porous carbon framework is 30-70%, preferably 40-60%. The thickness of the coating is 1~15 μm.

[0009] In some embodiments, the initial coulombic efficiency of the pre-lithiated anode is ≥95%.

[0010] A second aspect of this application provides a method for preparing the aforementioned pre-lithiated negative electrode, comprising: A carbonizable polymer, a prelithiation reagent, and a pore-forming agent are dispersed in a solvent to form a prelithiation slurry. The pre-lithiated slurry is coated onto at least a portion of the surface of the negative electrode substrate; The coated negative electrode substrate is heat-treated to form the coating.

[0011] Therefore, through heat treatment, the carbonizable polymer can be carbonized in situ to form a porous carbon framework, while the pore-forming agent decomposes to generate interconnected pores, and the pre-lithiation reagent is encapsulated within the walls of the porous carbon framework. Furthermore, the preparation method possesses all the characteristics and advantages of the aforementioned pre-lithiation anode sheet, which will not be elaborated further here.

[0012] In some embodiments, the preparation method satisfies at least one of the following conditions: The carbonizable polymer includes at least one of polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyimide (PI), polyvinyl alcohol (PVA), polyfurfuryl alcohol (PFA), phenolic resin, epoxy resin or asphalt, preferably at least one of polyacrylonitrile or polyvinylidene fluoride-hexafluoropropylene copolymer. The pore-forming agent includes at least one of a thermally decomposable pore-forming agent or a non-thermally decomposable pore-forming agent; preferably, the decomposition temperature of the thermally decomposable pore-forming agent is lower than the carbonization temperature of the carbonizable polymer; preferably, the non-thermally decomposable pore-forming agent can be removed by a post-treatment process. The pore-forming agent includes at least one of lithium chloride (LiCl), ammonium bicarbonate (NH4HCO3), ammonium oxalate ((NH4)2C2O4), sodium chloride (NaCl), ammonium carbonate ((NH4)2CO3), polymethyl methacrylate (PMMA), and polyvinyl alcohol (PVA), more preferably at least one of ammonium bicarbonate or lithium chloride.

[0013] In some embodiments, the mass ratio of the carbonizable polymer, the prelithiation reagent and the pore-forming agent in the prelithiation slurry is (1~10):(1~15):(0.5~5), preferably (2~6):(4~10):(1~3).

[0014] In some embodiments, the preparation method satisfies at least one of the following conditions: The solvent includes at least one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, and deionized water; The coating includes at least one of blade coating, spraying, dip coating, spin coating, and screen printing, preferably at least one of blade coating or spraying.

[0015] In some embodiments, the preparation method satisfies at least one of the following conditions: The heat treatment is carried out in an inert atmosphere, preferably, the inert atmosphere includes at least one of nitrogen (N2), argon (Ar), and helium (He); The heat treatment temperature is 250~500 ℃, preferably 300~450 ℃; The heat treatment holding time is 1-5 h, preferably 2-3 h; The heating rate of the heat treatment is 1~10 ℃ / min, preferably 2~5 ℃ / min.

[0016] A third aspect of this application provides a lithium-ion battery, including a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, wherein the negative electrode is the aforementioned pre-lithiated negative electrode or a pre-lithiated negative electrode prepared by the aforementioned preparation method.

[0017] Therefore, the lithium-ion battery possesses all the features and advantages of the aforementioned pre-lithiated negative electrode or preparation method, which will not be repeated here.

[0018] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation

[0019] The embodiments of this application are described in detail below. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0020] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this application, unless otherwise stated, "multiple" means two or more.

[0021] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0022] In this document, the terms “comprising” or “including” are open-ended expressions, meaning that they include the contents specified in this application but do not exclude other contents.

[0023] In this document, the terms “optionally,” “optionally,” or “optionally” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur.

[0024] This application is based on the inventor's following discoveries and understandings: In related technologies, electrochemical pre-lithiation drives lithium ions to embed into the negative electrode through an external power source, but it requires additional formation equipment and processes, has poor compatibility with traditional battery production lines, and is complex and time-consuming. Lithium foil rolling replenishment achieves lithium replenishment by pressing metallic lithium foil onto the surface of the negative electrode. However, metallic lithium is soft and easy to stick together, and the processing must be carried out in a strictly anhydrous and oxygen-free environment. In addition, the lithium foil utilization efficiency is low (usually less than 70%), and the uniformity of lithium replenishment is difficult to guarantee. The lithium powder spraying method requires the stable lithium powder to be dispersed and sprayed onto the surface of the electrode. However, lithium powder is extremely sensitive to moisture, and the dew point of the production environment must be below -50°C, which poses a high operational risk. At the same time, it places stringent requirements on the sealing of the coating equipment. Chemical pre-lithiation involves impregnating the electrode with a solution of highly active organic lithium reagents (such as n-butyllithium, biphenyl lithium, etc.). However, this process involves a large amount of organic solvents, which puts great pressure on the environment. Moreover, the degree of lithiation is greatly affected by factors such as reaction time and concentration, making it difficult to achieve precise control. Bulk pre-lithiation of materials is mainly achieved by introducing a lithium source during the synthesis stage of the anode active material. This strategy has been applied in silicon-based anodes, but its applicability to graphite anodes is limited, and the amount of pre-lithiation is fixed, making it difficult to adjust flexibly according to the actual battery system.

[0025] The inventors discovered that the root cause of the above problems lies in the fact that the pre-lithiation reagent is directly exposed to the processing environment during the preparation and storage of the electrode, and lacks an effective in-situ physical isolation and protection mechanism.

[0026] Based on the above research, the inventors have developed a new pre-lithiation anode sheet and its preparation method and application, which can precisely control the degree of pre-lithiation and has the characteristics of high lithium source utilization efficiency, good environmental compatibility and simple process.

[0027] The first aspect of this application provides a pre-lithiated negative electrode, comprising: Negative electrode substrate; and A coating disposed on at least a portion of the surface of the negative electrode substrate; The coating comprises a porous carbon skeleton having interconnected pores that communicate with the outside of the coating, and a pre-lithiation reagent is embedded in the wall of the porous carbon skeleton.

[0028] Therefore, by connecting the pores, the pre-lithiated negative electrode sheet serves two purposes: firstly, it acts as a rapid permeation channel for the electrolyte during the electrolyte injection stage, significantly shortening the static activation time; secondly, it serves as a transport channel for lithium-ion insertion / extraction and a release space for volume expansion during electrochemical cycling. The pre-lithiation reagent is encapsulated within the porous carbon framework, preventing deactivation during processing and storage; the lithium replenishment process is carried out uniformly, avoiding local over-lithiation or under-lithiation problems; the carbon framework, as a physical isolation layer, facilitates the relaxation of dew point requirements in the production environment, significantly improving operational safety. More importantly, the interconnected pores and the embedded pre-lithiation reagent are independent yet synergistic, giving the coating both excellent air storage stability and rapid electrochemical activation response, high lithium source utilization, and controllable pre-lithiation degree. This overcomes the technical bias of traditional pre-lithiated coatings where better protection leads to slower activation, thus improving initial coulombic efficiency and significantly extending cycle life. This application is based on conventional processes such as coating and heat treatment, with a simple process that is easy to integrate into relevant electrode manufacturing processes without requiring large-scale production line modifications and exhibiting good compatibility with traditional production lines.

[0029] After the pre-lithiated negative electrode is injected into contact with the electrolyte, the pre-lithiation reagent decomposes and releases lithium ions (Li). + ), Li + The lithium ions can diffuse through the interstices of the carbon lattice in the porous carbon framework wall into the interconnected pores and migrate with the electrolyte to the surface of the negative electrode substrate for lithium replenishment. This solid-state diffusion path allows lithium ions to pass through, while water and oxygen molecules in the external environment are effectively blocked because their kinetic diameters are larger than the interstices of the carbon lattice. This effectively improves the stability of the pre-lithiated reagent embedded in the porous carbon framework wall during storage.

[0030] This invention does not impose any particular limitation on the type of electrolyte, and conventional lithium-ion battery electrolytes known in the art can be used. Specifically, the electrolyte comprises lithium salt and organic solvent. There are no particular limitations on the contact method between the pre-lithiated negative electrode and the electrolyte, as long as the electrolyte can wet the coating on the surface of the pre-lithiated negative electrode. For example, the pre-lithiated negative electrode can be directly immersed in the electrolyte, allowing the electrolyte to penetrate into the porous carbon framework through interconnected pores, contacting the pre-lithiating reagent embedded in the wall and triggering the release and insertion of lithium ions; alternatively, the pre-lithiated negative electrode can be assembled with the positive electrode and separator into a battery cell, and then the electrolyte can be injected. Under static conditions, the electrolyte spontaneously wets the coating and triggers the release and insertion of lithium ions, or an electric field can be used to assist in promoting the release and insertion of lithium ions during the first charge.

[0031] In some embodiments, the negative electrode substrate includes at least one of a carbon-based negative electrode substrate, a silicon-based negative electrode substrate, a tin-based negative electrode substrate, or a composite negative electrode substrate thereof; preferably, the negative electrode substrate is a graphite negative electrode substrate.

[0032] In some embodiments, the coating thickness is 1–15 μm; specifically, it can be 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 13 μm, 15 μm, etc. This helps to form a continuous and uniform pre-lithiation functional layer on the surface of the negative electrode substrate, providing sufficient pre-lithiation reagent capacity without excessively increasing the electrode resistance. If the coating is too thin, it may be difficult to adequately compensate for irreversible lithium loss during the first charge; if the coating is too thick, it may prolong the lithium ion migration path, leading to poorer lithium replenishment kinetics and increased volumetric energy density loss.

[0033] In some embodiments, the BET specific surface area of ​​the porous carbon framework is 50~400 m². 2 / g, preferably 100~300m 2 / g; specifically, it can be 50 m 2 / g、80 m 2 / g、100 m 2 / g, 150 m 2 / g、200 m 2 / g、250 m 2 / g、300 m 2 / g、350 m 2 / g、400 m 2 / g etc. This facilitates the formation of sufficient porous structures within the carbon framework, providing ample interfacial area for electrolyte wetting and lithium-ion transport, while also offering suitable adhesion and containment space for pre-lithiation reagents. If the BET specific surface area is too low, it may reduce the electrolyte penetration rate, thereby decreasing lithium replenishment efficiency; if the BET specific surface area is too high, it may weaken the mechanical strength of the framework, leading to easy powdering or cracking of the coating during cycling.

[0034] In some embodiments, the pore size of the porous carbon framework is 2-50 nm, preferably 5-30 nm; specifically, it can be 2 nm, 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 40 nm, 50 nm, etc. This facilitates the smooth penetration of the electrolyte into the interconnected pores while providing a suitable diffusion path for lithium ion insertion / extraction. If the pore size is too large, the pre-lithiation reagent may be released too quickly after electrolyte injection, making the lithium replenishment process difficult to control; if the pore size is too small, it may hinder electrolyte wetting, reduce the migration rate of lithium ions, and decrease lithium utilization.

[0035] In some embodiments, the porosity of the porous carbon skeleton is 30-70%, preferably 40-60%; specifically, it can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc. Controlling the porosity within the above range helps to construct sufficient lithium storage space and ion transport channels within the coating, while also maintaining the structural integrity of the carbon skeleton. If the porosity is too low, the electrolyte may not wet sufficiently, increasing the resistance to lithium-ion diffusion and weakening the lithium replenishment effect; if the porosity is too high, the carbon skeleton walls may be too thin, reducing its structural strength and making it prone to channel collapse during electrode processing or battery cycling, thus reducing stability.

[0036] It is understood that this application does not impose any particular limitation on the type of pre-lithiation reagent, as long as the pre-lithiation reagent can release lithium ions under appropriate conditions (e.g., after contact with the electrolyte) to achieve lithium replenishment of the graphite anode. For example, the pre-lithiation reagent may include at least one of stabilized lithium metal (SLMP), lithium hydride (LiH), lithium silicon alloy, lithium tin alloy, and lithium aluminum alloy, or other lithium-containing compounds known in the art that can release active lithium may be used.

[0037] It should be noted that, in this document, the term "stabilized lithium metal" refers to lithium metal powder with a passivation layer on its surface. This passivation layer physically isolates the lithium metal from the external environment, thereby reducing its reactivity and improving its stability in dry air. Specifically, the stabilized lithium metal powder comprises a lithium metal core and a passivation layer coating the surface of the lithium metal core; optionally, the passivation layer comprises at least one of a lithium carbonate layer, a lithium fluoride layer, and a lithium phosphate layer.

[0038] The passivation layer prevents external moisture and oxygen from directly contacting the core lithium metal, thereby suppressing side reactions and allowing the stabilized lithium metal powder to be handled and processed in a conventional dry environment. Upon contact with an electrolyte, the passivation layer of the stabilized lithium metal powder can be disrupted by components in the electrolyte (such as trace amounts of moisture, acids, or specific additives), or lithium ions can be released under the influence of an applied electric field / lithium concentration gradient, thus replenishing lithium to the graphite anode.

[0039] In some embodiments, the average particle size of the pre-lithiation reagent is 10 nm to 50 μm, preferably 1 to 100 μm; specifically, it can be 10 nm, 50 nm, 100 nm, 200 nm, 500 nm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, etc. This facilitates the effective embedding of the pre-lithiation reagent within the wall. If the average particle size of the pre-lithiation reagent is too large, it may be difficult for the pre-lithiation reagent to be completely encapsulated by the carbon framework wall during heat treatment, easily leading to deactivation of the pre-lithiation reagent in subsequent processes; if the average particle size is too small, it may cause uneven dispersion of the pre-lithiation reagent in the slurry, resulting in agglomeration and reducing the uniformity of the pre-lithiation reagent distribution in the coating.

[0040] In some embodiments, the initial coulombic efficiency of the pre-lithiated anode sheet is ≥95%; specifically, it can be 95%, 96%, 97%, 98%, 99%, etc. Initial coulombic efficiency is one of the core indicators for evaluating the pre-lithiation effect. Controlling it within the above range indicates that the pre-lithiation reagent maintains good activity during processing and storage, and can be fully released and embedded in the graphite anode after liquid injection. A higher initial coulombic efficiency helps reduce irreversible capacity loss during the first charge and discharge process, thereby improving the initial energy density and cycle life of the battery.

[0041] A second aspect of this application provides a method for preparing the aforementioned pre-lithiated negative electrode, comprising: A carbonizable polymer, a prelithiation reagent, and a pore-forming agent are dispersed in a solvent to form a prelithiation slurry. The pre-lithiated slurry is coated onto at least a portion of the surface of the negative electrode substrate; The coated negative electrode substrate is heat-treated to form the coating.

[0042] Therefore, the carbonizable polymer can be carbonized in situ to form a porous carbon framework through a single heat treatment, while the pore-forming agent decomposes to create interconnected pores, and the pre-lithiation reagent is encapsulated within the walls of the porous carbon framework. This application is based on conventional processes such as coating and heat treatment; it only requires mixing and coating the carbonizable polymer, pre-lithiation reagent, and pore-forming agent followed by a single heat treatment, eliminating the need for multi-step operations. The process is simple, easy to integrate into relevant electrode manufacturing processes, requires no large-scale production line modifications, and has good compatibility with traditional production lines.

[0043] It should be noted that pre-lithiation reagents (such as Li₂CO₃, LiOH, or organolithium compounds) are generally heat-sensitive and difficult to maintain stability during pore-forming agent decomposition and polymer carbonization. Therefore, conventional processes often employ a step-by-step strategy: first, carbonization is performed to construct a carbon framework, and then the pre-lithiation reagent is introduced through liquid-phase impregnation or vapor-phase deposition. While this step-by-step approach avoids the problem of direct thermal deactivation of the pre-lithiation reagent, it increases process complexity and manufacturing costs. Furthermore, the subsequently introduced lithium source usually only adheres to the surface of the carbon framework or the pore walls, making it difficult to effectively encapsulate within the carbon walls. This results in the lithium source still being susceptible to deactivation due to contact with environmental moisture during subsequent processing and storage, thus limiting the lithium replenishment effect and lithium source utilization.

[0044] This application achieves three functions in one step: blending a carbonizable polymer, a pre-lithiation reagent, and a pore-forming agent followed by heat treatment. By precisely matching the carbonization temperature of the carbonizable polymer, the decomposition temperature of the pore-forming agent, and the thermal stability temperature of the pre-lithiation reagent, a thermal decomposition temperature gradient is formed among the three. This allows the pore-forming agent to decompose before or simultaneously with the carbonization process, generating interconnected pores. At the same time, it ensures that the pre-lithiation reagent does not decompose or become deactivated during the heat treatment process and is coated by the simultaneously generated porous carbon framework wall. Thus, it combines the functions of pore formation, carbonization, and lithium source encapsulation in the same process, eliminating the need for separate steps. This simplifies the process, improves lithium source utilization, and enhances lithium replenishment.

[0045] Furthermore, the preparation method described above possesses all the characteristics and advantages of the aforementioned pre-lithiated negative electrode sheet, which will not be repeated here.

[0046] It is understood that this application does not impose any particular limitation on the type of carbonizable polymer, as long as the carbonizable polymer can undergo carbonization under heat treatment conditions to form amorphous carbon or graphite-like carbon skeleton. For example, the carbonizable polymer may include at least one of polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyimide (PI), polyvinyl alcohol (PVA), polyfurfuryl alcohol (PFA), phenolic resin, epoxy resin, or asphalt, preferably at least one of polyacrylonitrile or polyvinylidene fluoride-hexafluoropropylene copolymer. The above-mentioned carbonizable polymer can undergo pyrolysis crosslinking and carbonization reactions during high-temperature treatment to form a continuous three-dimensional carbon network structure, which is beneficial for embedding pre-lithiated reagents inside the carbon skeleton wall, while providing a suitable pore formation environment for the decomposition of pore-forming agents.

[0047] This application does not impose any particular limitation on the type of pore-forming agent, as long as the pore-forming agent can leave interconnecting channels in the porous carbon framework. Specifically, the pore-forming agent includes at least one of thermally decomposable pore-forming agents or non-thermally decomposable pore-forming agents; for example, the pore-forming agent may include at least one of lithium chloride (LiCl), ammonium bicarbonate (NH4HCO3), ammonium oxalate ((NH4)2C2O4), sodium chloride (NaCl), ammonium carbonate ((NH4)2CO3), polymethyl methacrylate (PMMA), and polyvinyl alcohol (PVA), preferably at least one of ammonium bicarbonate or lithium chloride.

[0048] It should be understood that the thermally decomposable pore-forming agent can decompose to generate gas during heat treatment, thereby forming interconnected pores between the carbon skeleton walls; the non-thermally decomposable pore-forming agent does not decompose at the heat treatment temperature, but is removed during post-treatment to form interconnected pores. Those skilled in the art can select appropriate pore-forming agent types and combinations according to actual process requirements.

[0049] Preferably, the decomposition temperature of the pore-forming agent is lower than the carbonization temperature of the carbonizable polymer. This facilitates the formation of channels before the carbon skeleton densifies. As the carbonization temperature further increases, the carbon skeleton solidifies around the channels, forming a connected pore structure that communicates with the outside of the coating. This ensures an orderly temporal connection between the pore-forming and carbonization processes, improving the structural controllability of the coating. If the decomposition temperature of the pore-forming agent is too high, the carbon skeleton may have already largely solidified and shrunk before the pore-forming agent decomposes. The gas generated by the decomposition of the pore-forming agent will be unable to form effective interconnected channels in the already densified carbon walls, resulting in low porosity or non-connected channels, reducing the subsequent electrolyte wetting and lithium-ion transport efficiency.

[0050] Preferably, the non-pyrolytic pore-forming agent can be removed by a post-treatment process; specifically, the post-treatment process includes washing with water 2 to 5 times.

[0051] In some embodiments, the mass ratio of the carbonizable polymer, the prelithiation reagent, and the pore-forming agent in the prelithiation slurry is (1~10):(1~15):(0.5~5), preferably (2~6):(4~10):(1~3); specifically, it can be 1:1:0.5, 1:5:1, 2:4:1, 3:6:1.5, 4:8:2, 5:10:2.5, 6:10:3, 8:12:4, 10:15:5, etc. This facilitates the formation of a continuous and dense porous carbon framework during heat treatment, while ensuring that the prelithiation reagent is fully and uniformly embedded within the carbon framework wall, providing sufficient lithium replenishment capacity for the negative electrode. Simultaneously, it forms an appropriate number and size of interconnected pores in the carbon framework, providing unobstructed channels for electrolyte wetting and lithium-ion transport.

[0052] It is understood that the present invention does not impose any particular limitation on the type of solvent, as long as it can sufficiently dissolve or disperse the carbonizable polymer. For example, the solvent may include at least one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, and deionized water. The above solvents have good solubility or dispersibility for carbonizable polymers, which is beneficial for forming a uniform and stable pre-lithiation slurry, thereby providing a good film-forming basis for subsequent coating processes. Those skilled in the art can select the appropriate solvent based on the solubility characteristics of the carbonizable polymer.

[0053] In some embodiments, the coating includes at least one of blade coating, spraying, dip coating, spin coating, and screen printing, preferably at least one of blade coating or spraying.

[0054] In some embodiments, the preparation method further includes drying the coated negative electrode substrate before heat treatment.

[0055] Furthermore, the drying process includes drying at 60~90 ℃ for 1~3 h; specifically, the drying temperature can be 60 ℃, 65 ℃, 70 ℃, 75 ℃, 80 ℃, 85 ℃, 90 ℃, etc.; the drying time can be 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.

[0056] This allows for more complete evaporation of the solvent in the pre-lithiated slurry before heat treatment, reducing the impact of residual solvent in the coating on the subsequent carbonization process. If the drying temperature is too low or the drying time is too short, the rapid evaporation of residual solvent during subsequent heat treatment may cause bubbles or cracks in the coating, which is detrimental to the integrity of the carbon skeleton structure and affects the purity of the carbonized product. If the drying temperature is too high or the drying time is too long, side reactions may occur, affecting the controllability of the carbon skeleton structure during subsequent carbonization.

[0057] In some embodiments, the heat treatment is performed in an inert atmosphere. This helps to suppress unnecessary side reactions during carbonization, resulting in a more ordered and dense microstructure of the carbon skeleton, while reducing the introduction of impurity elements. The present invention does not particularly limit the type of inert atmosphere used for the heat treatment, as long as it can provide an oxygen-free or low-oxygen environment for the carbonization process of the carbonizable polymer. For example, the inert atmosphere may include at least one of nitrogen (N2), argon (Ar), and helium (He). The aforementioned inert atmosphere effectively isolates the carbonizable polymer from air or oxygen, preventing oxidation and ablation during high-temperature carbonization, and avoiding deactivation of the pre-lithiation reagent due to oxidation, thereby improving the structural integrity of the carbon skeleton and the activity retention capacity of the pre-lithiation reagent.

[0058] In some embodiments, the temperature of the heat treatment is 250~500 ℃, preferably 300~450 ℃; specifically, it can be 250 ℃, 280 ℃, 300 ℃, 350 ℃, 400 ℃, 420 ℃, 450 ℃, 500 ℃, etc.

[0059] In some embodiments, the heat treatment holding time is 1 to 5 hours, preferably 2 to 3 hours; specifically, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 5 hours, etc.

[0060] In some embodiments, the heating rate of the heat treatment is 1~10 ℃ / min, preferably 2~5 ℃ / min; specifically, it can be 1 ℃ / min, 2 ℃ / min, 3 ℃ / min, 4 ℃ / min, 5 ℃ / min, 6 ℃ / min, 8 ℃ / min, 10 ℃ / min, etc.

[0061] Controlling the heat treatment temperature, holding time, and heating rate within the above range is beneficial for the carbonizable polymer to be fully carbonized to form a relatively complete porous carbon skeleton. At the same time, it allows the pore-forming agent to decompose and release gas to form interconnected pores, and keeps the pre-lithiated reagent stable inside the carbon skeleton wall and effectively embedded.

[0062] If the heat treatment temperature is too low, the carbonizable polymer may not be carbonized sufficiently, reducing the density and mechanical strength of the carbon skeleton. If the heat treatment temperature is too high, the carbon skeleton may shrink excessively, the interconnected pores may be compressed or even closed, and some pre-lithiated reagents may decompose or become inactive due to overheating.

[0063] If the holding time is too short, the carbonization of the carbonizable polymer may be incomplete, which is not conducive to the formation of a continuous and stable carbon skeleton structure. If the holding time is too long, the carbon skeleton may be further graphitized or excessively shrunk, resulting in a decrease in porosity.

[0064] If the heating rate is too fast, it may cause uneven shrinkage stress inside the carbon skeleton, which may easily lead to coating cracking or peeling from the negative electrode substrate; if the heating rate is too slow, the gaseous byproducts generated by the decomposition of the pore-forming agent during the heating process may affect the uniformity of the carbon skeleton structure due to the long residence time.

[0065] A third aspect of this application provides a lithium-ion battery, including a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, wherein the negative electrode is the aforementioned pre-lithiated negative electrode or a pre-lithiated negative electrode prepared by the aforementioned preparation method.

[0066] Therefore, the lithium-ion battery possesses all the features and advantages of the aforementioned pre-lithiated negative electrode or preparation method, which will not be repeated here.

[0067] In some embodiments, the positive electrode sheet comprises a positive electrode active material; specifically, the positive electrode active material includes at least one of lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), nickel cobalt manganese ternary material (NCM), nickel cobalt aluminum ternary material (NCA), lithium manganese oxide (LiMn2O4), and lithium-rich manganese-based material.

[0068] This invention does not impose any particular limitation on the form of the lithium-ion battery, which can be selected according to actual application requirements. For example, the lithium-ion battery can be any one of a pouch battery, a cylindrical battery, or a prismatic battery. The above-mentioned battery forms are all mature and widely used battery structures in the field, and the pre-lithiated negative electrode sheet can play its lithium replenishment role in these battery systems, thus having a wide range of applications.

[0069] The following will explain the solution of this application with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0070] Example 1 A method for preparing a pre-lithiated negative electrode sheet, comprising: (1) Preparation of prelithiation slurry In a nitrogen-protected glove box (moisture content <1 ppm, oxygen content <1 ppm), weigh the following raw materials: PAN (weight average molecular weight approximately 150,000) 0.3 g, SLMP (average particle size 50 μm, Li content >98%, surface coated with Li2CO3 layer) 0.6 g, NH4HCO3 0.1 g, NMP 5 mL; PAN was added to NMP and magnetically stirred at 60°C for 2 hours to completely dissolve it; then SLMP and NH4HCO3 were added sequentially and stirred for another hour to form a pre-lithiated slurry (the mass ratio of PAN, SLMP and NH4HCO3 in the slurry was 3:6:1). (2) Coating and drying Commercial graphite anode sheets (BETRY commercially available graphite anode sheets, areal density approximately 10 mg / cm³) 2 The pre-lithiated slurry (pre-rolled) is used as the negative electrode substrate; the pre-lithiated slurry is uniformly coated on the surface of the graphite negative electrode sheet using a doctor blade coating method, with a doctor blade gap of 50 μm and a coating speed of 1.2 m / min. The coated electrode was placed in a vacuum drying oven and dried at 80°C for 2 hours. (3) In-situ solid-phase carbonization The dried electrode was placed in a tube furnace and heated from room temperature to 350°C at a rate of 5°C / min under an argon atmosphere (argon flow rate of 100 mL / min). It was then heat-treated at 350°C for 2 hours and then naturally cooled to room temperature to form a coating, thus obtaining the pre-lithiated negative electrode with a coating thickness of approximately 3 μm.

[0071] Example 2 A method for preparing a pre-lithiated negative electrode sheet, comprising: (1) Preparation of prelithiation slurry In a nitrogen-protected glove box (moisture content <1 ppm, oxygen content <1 ppm), weigh the following raw materials: 0.4 g of PVDF-HFP (weight average molecular weight approximately 400,000, HFP content approximately 15 wt%), 0.8 g of LiH (average particle size approximately 30 μm, purity >98%), 0.2 g of PMMA microspheres, and 6 mL of NMP; PVDF-HFP was added to NMP and magnetically stirred at 50°C for 3 hours until completely dissolved; then LiH and PMMA microspheres were added sequentially and stirred for another 1.5 hours to form a pre-lithiated slurry (the mass ratio of PVDF-HFP, LiH and PMMA microspheres in the slurry was 4:8:2). (2) Coating and drying Commercial graphite anode sheets (area density approximately 10 mg / cm³) 2 The pre-lithiated slurry (pre-rolled) is used as the negative electrode substrate; the pre-lithiated slurry is uniformly coated on the surface of the graphite negative electrode sheet using a doctor blade coating method, with a doctor blade gap of 50 μm and a coating speed of 1.2 m / min. The coated electrode was placed in a vacuum drying oven and dried at 80°C for 2 hours. (3) In-situ solid-phase carbonization The dried electrode was placed in a tube furnace and heated from room temperature to 420°C at a rate of 3°C / min under an argon atmosphere (argon flow rate of 100 mL / min). It was then heat-treated at 420°C for 2.5 h and then naturally cooled to room temperature to form a coating, thus obtaining the pre-lithiated negative electrode with a coating thickness of approximately 3.6 μm.

[0072] Example 3 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the mass ratio of PAN, SLMP and NH4HCO3 in the slurry in this embodiment is 4:4:1.

[0073] Example 4 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the mass ratio of PAN, SLMP and NH4HCO3 in the slurry in this embodiment is 3:6:1.

[0074] Example 5 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the mass ratio of PAN, SLMP and NH4HCO3 in the slurry in this embodiment is 2:8:1.

[0075] Example 6 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the mass ratio of PAN, SLMP and NH4HCO3 in the slurry in this embodiment is 1:10:1.

[0076] Comparative Example 1 This comparative example uses the commercial graphite anode sheet described in Example 1, directly as the anode sheet without any processing.

[0077] Comparative Example 2 This comparative example uses a lithium foil calendering method to pre-lithiate the commercial graphite anode sheet described in Example 1, specifically including: In an argon-filled glove box, a 20 μm thick lithium metal foil was applied to the surface of the graphite anode sheet at a pressure of 60 kg / cm². 2 The pressure roller is used for compounding, and the pre-lithiation is completed after standing for 24 hours.

[0078] Application Example 1 The pre-lithiated negative electrode sheets described in Examples 3-6 were assembled with the counter electrode into a coin cell under an inert atmosphere, and then injected with 1 mol / L LiPF6 / EC / EMC electrolyte (volume ratio 1:1:1) and allowed to stand for 12 hours.

[0079] Application Example 2 The negative electrode sheets described in Examples 1-2 and Comparative Examples 1-2 were assembled with a positive electrode sheet, a separator, and an electrolyte to form a full cell (pouch cell) with a designed capacity of approximately 2.5 Ah. The positive electrode used a commercial lithium iron phosphate (LiFePO4) electrode sheet with an areal density of approximately 20 mg / cm³. 2 The diaphragm used was Celgard 2400; the electrolyte was a 1 mol / L LiPF6 EC / EMC / DMC solution (volume ratio 1:1:1).

[0080] Performance testing 1. Test the initial coulombic efficiency of each coin cell half-cell described in Application Example 1 using the following method: At 25°C, perform a constant current charge-discharge test at a rate of 0.1 C, with a voltage range of 0.01~1.5 V (coin cell half-cell, counter electrode is lithium metal). Record the initial charge specific capacity (lithiation process) and the initial discharge specific capacity (delithiation process). Calculate the initial coulombic efficiency using the following formula: Initial coulombic efficiency (%) = (Initial discharge specific capacity / Initial charge specific capacity) × 100% The results showed that the initial coulombic efficiencies of Examples 3-6 were 91.5%, 95.2%, 96.9%, and 97.8%, respectively. This indicates that the present invention can precisely control the degree of pre-lithiation by adjusting the slurry formulation.

[0081] 2. The electrochemical performance of each soft-pack battery described in Example 2 shall be tested according to the following method, and the results shall be recorded in Table 1.

[0082] 1) Initial Coulombic Efficiency: Charge-discharge tests were conducted at 25°C with a voltage range of 2.5~3.65 V. The initial discharge specific capacity and initial charge specific capacity were obtained, and the initial coulombic efficiency was calculated using the following formula: Initial coulombic efficiency (%) = (Initial discharge specific capacity / Initial charge specific capacity) × 100% 2) Capacity retention rate: After cycling at 1C for 500 cycles, the discharge specific capacity after the 500th cycle is obtained. The capacity retention rate is calculated using the following formula: Capacity retention rate (%) = (Specific capacity at 500th discharge cycle / Specific capacity at initial discharge cycle) × 100% 3) Lithium source utilization rate: The lithium source utilization rate of the pouch battery is calculated using the following formula: Lithium source utilization rate (%) = (Q 空白首圈不可逆 - Q 预锂化首圈不可逆 ) / Q 理论预锂化 × 100% in: Q 空白首圈不可逆 Q refers to the irreversible capacity loss in the first pass of a blank graphite anode (without pre-lithiation treatment). 空白首圈不可逆 = Initial charge specific capacity of blank negative electrode - Initial discharge specific capacity of blank negative electrode; Q 预锂化首圈不可逆 This refers to the irreversible capacity loss in the first cycle of the pre-lithiated negative electrode described in this invention, Q. 预锂化首圈不可逆 = First charge specific capacity of pre-lithiated anode - First discharge specific capacity of pre-lithiated anode; Q 理论预锂化 It refers to the capacity of lithium contained in the pre-lithiation reagent in the pre-lithiation slurry coated on the surface of the negative electrode substrate, calculated according to the theoretical electrochemical equivalent.

[0083] 3. Activity Retention Rate: After the pre-lithiated electrode was placed at -40℃ dew point for 48 h, it was assembled into a coin cell using the above process and testing methods. The initial coulombic efficiency of the half-cell was tested, and its activity retention rate was calculated according to the following formula: Activity retention rate (%) = Activity retention rate (%) = Initial coulombic efficiency of half-cell assembled with electrodes after 48 hours of dew point exposure / Initial coulombic efficiency of half-cell assembled with fresh electrodes × 100% Table 1 Electrochemical performance test results

[0084] Note: The lithium foil rolled pre-lithiated electrode of Comparative Example 2 showed obvious oxidation and discoloration on its surface after being placed at a dew point of -40℃ for 2 hours, and could not be tested for 48 hours. Therefore, its activity retention rate is marked as " / ".

[0085] The results showed that the initial coulombic efficiency, lithium source utilization, and capacity retention of Examples 1-2 were significantly better than those of Comparative Examples 1-2, and they also exhibited excellent activity retention. In contrast, Comparative Example 2 showed obvious surface oxidation and discoloration after being placed at the dew point for 2 hours. This demonstrates that the method of the present invention is significantly superior to related technologies in terms of initial coulombic efficiency, lithium source utilization, cycle stability, and environmental compatibility.

[0086] In the description of this specification, the references to terms such as "an embodiment," "some embodiments," "a method of implementation," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0087] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A pre-lithiated negative electrode, characterized in that, include: Negative electrode substrate; as well as A coating disposed on at least a portion of the surface of the negative electrode substrate; The coating comprises a porous carbon skeleton having interconnected pores that communicate with the outside of the coating, and a pre-lithiation reagent is embedded in the wall of the porous carbon skeleton.

2. The pre-lithiated negative electrode sheet according to claim 1, characterized in that, At least one of the following conditions must be met: The negative electrode substrate includes at least one of carbon-based negative electrode substrate, silicon-based negative electrode substrate, tin-based negative electrode substrate, or a composite negative electrode substrate thereof; preferably, the negative electrode substrate is a graphite negative electrode substrate; The pre-lithiation reagent includes at least one of stabilized lithium metal, lithium hydride, lithium silicon alloy, lithium tin alloy, and lithium aluminum alloy; The average particle size of the pre-lithiation reagent is 10 nm to 50 μm, preferably 1 to 100 μm.

3. The pre-lithiated negative electrode sheet according to claim 1, characterized in that, At least one of the following conditions must be met: The porous carbon framework has a BET specific surface area of ​​50~400 m². 2 / g, preferably 100~300 m 2 / g; The porous carbon framework has a pore size of 2~50 nm, preferably 5~30 nm; The porosity of the porous carbon framework is 30-70%, preferably 40-60%. The thickness of the coating is 1~15 μm.

4. The pre-lithiated negative electrode sheet according to claim 1, characterized in that, The initial coulombic efficiency of the pre-lithiated anode sheet is ≥95%.

5. A method for preparing a pre-lithiated negative electrode sheet as described in any one of claims 1 to 4, characterized in that, include: A carbonizable polymer, a prelithiation reagent, and a pore-forming agent are dispersed in a solvent to form a prelithiation slurry. The pre-lithiated slurry is coated onto at least a portion of the surface of the negative electrode substrate; The coated negative electrode substrate is heat-treated to form the coating.

6. The preparation method according to claim 5, characterized in that, At least one of the following conditions must be met: The carbonizable polymer includes at least one of polyacrylonitrile, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyimide, polyvinyl alcohol, polyfurfuryl alcohol, phenolic resin, epoxy resin or asphalt, preferably at least one of polyacrylonitrile or polyvinylidene fluoride-hexafluoropropylene copolymer; The pore-forming agent includes at least one of a thermally decomposable pore-forming agent or a non-thermally decomposable pore-forming agent; preferably, the decomposition temperature of the thermally decomposable pore-forming agent is lower than the carbonization temperature of the carbonizable polymer; preferably, the non-thermally decomposable pore-forming agent can be removed by a post-treatment process. The pore-forming agent includes at least one of lithium chloride, ammonium bicarbonate, ammonium oxalate, sodium chloride, ammonium carbonate, polymethyl methacrylate, and polyvinyl alcohol, more preferably at least one of ammonium bicarbonate or lithium chloride.

7. The preparation method according to claim 5, characterized in that, In the prelithiation slurry, the mass ratio of the carbonizable polymer, the prelithiation reagent and the pore-forming agent is (1~10):(1~15):(0.5~5), preferably (2~6):(4~10):(1~3).

8. The preparation method according to claim 5, characterized in that, At least one of the following conditions must be met: The solvent includes at least one of N-methylpyrrolidone, dimethylformamide, dimethyl sulfoxide, ethanol, and deionized water; The coating includes at least one of blade coating, spraying, dip coating, spin coating, and screen printing, preferably at least one of blade coating or spraying.

9. The preparation method according to claim 5, characterized in that, At least one of the following conditions must be met: The heat treatment is carried out in an inert atmosphere, preferably including at least one of nitrogen, argon, and helium. The heat treatment temperature is 250~500 ℃, preferably 300~450 ℃; The heat treatment holding time is 1-5 h, preferably 2-3 h; The heating rate of the heat treatment is 1~10 ℃ / min, preferably 2~5 ℃ / min.

10. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, wherein the negative electrode is a pre-lithiated negative electrode as described in any one of claims 1 to 4 or a pre-lithiated negative electrode prepared by the preparation method described in any one of claims 5 to 9.